Return on Service Amenities. (February 2017) - Hamilton, Rebecca W.; Rust, Roland T.; Wedel, Michel; Dev, Chekitan S.
Firms often vie for competitive advantage by providing additional services (amenities)to their customers. Although extant research has focused on the effect of adding amenities on choice, return on service amenities may arise from two sources: increased initial choice and increased revenues from repurchase. The authors develop a return on investment (ROI) model to capture how service amenities produce financial return from these two sources. They apply the model to hotel amenities, using a discrete choice experiment and a large-scale customer database developed in collaboration with a multibrand global hotel company. The authors employ a hierarchical Bayesian formulation to estimate the parameters. They use the estimation results to compare ROI for three amenities for six brands and find that returns vary across amenities, and returns on a single amenity can vary substantially across brands. The authors validate the results for one amenity against the ROI from the actual historical implementation of that amenity using a natural experiment with a before/after design with controls. The present research demonstrates that the return on service amenities model provides a useful decision tool for managers deciding which amenities are most profitable.